Inbreeding: when parents transmit more than genes. - Szulkin, M; Sheldon, B (2006)
Inbreeding in wild populations can have devastating effects on fitness, but the genetic causes should not be transmitted across generations. A new study of song sparrows has revealed a parent-offspring resemblance for inbreeding, resulting from population structuring, with important implications for understanding the genetic causes of phenotypic variation in wild populations.